Characterization of Drought-Responsive Transcriptome During Seed Germination in Adzuki Bean (Vigna angularis L.) by PacBio SMRT and Illumina Sequencing - Zhu, Zhenzhen; Chen, Hongwei; Xie, Ke; Liu, Changyan; Li, Li; Liu, Liangjun; Han, Xuesong; Jiao, Chunhai; Wan, Zhenghuang; Sha, Aihua (Frontiers in Genetics, 2020)
The full-length single-molecular sequencing and short reads Illumina sequencing were combined to generate the transcripts of adzuki bean with high-quality. A total of 17,636 loci and 60,454 transcripts were detected in this study. To characterize the drought-responsive genes during seed germination in adzuki bean, two varieties, i.e., tolerant and sensitive to drought stress, were selected to conduct analysis of alternative splicing dynamics (AS) and differentially expressed genes (DEGs) by combining the newly assembled draft genome and public adzuki bean reference genome. AS analysis indicated that both the two varieties underwent a little more AS events under control conditions than under drought stress. Among the AS events, IR (intron retention) predominately accounted for 34.3%, whereas AD（alternative donor site）was the least frequent with 15.8%. Meanwhile, 562 long non-coding RNAs, 409 fusion genes and 1208 transcription factors were identified. Moreover, a total of 5,337 DEGs were identified in comparison of the two varieties with drought or control treatments. Notably, 82 DEGs were discovered in the two varieties under drought stress, which might be the candidate in regulation of seed germination to answer for different drought tolerance. The DEGs encoded proteins involved in primary or second metabolism, plant hormone signal transduction, transcript or translation processes, ubiquitin proteasome system, transcription factor, transporters, and so on. The results facilitate to increase the knowledge about the mechanism of drought tolerance during crop seed germination, and provide reference for the breeding of drought-tolerant adzuki bean.